A Web service Based Multi Agent System for the Diagnosis of industrial plants, May, ISSN/ISBN 1970 – 8734/1970-8742 - Chouhal Ouahiba; Mouss Leila Hayet; Mahdaoui Rafik (IREME International Review of Mechanical Engineering., 2013)
Fault diagnosis and maintenance are considered as vital aspects in industrial process, therefore, fault diagnosis systems should support decision-making tools, new diagnosis approaches and technique. In this paper, we discuss the cooperation of agents and Web Services in order to create highly flexible and dynamic framework for manufacturing systems fault diagnosis based on three-tier architectures that can support a distributed application. We depict also how Web Services can be located and the provided services can be invoked.